THE EFFECT OF THE NUMBER OF TOURISTS, NUMBER OF RESTAURANTS, AND HOTEL OCCUPANCY RATES ON REGIONAL TAX REVENUE IN REGENCIES/CITIES IN EAST NUSA TENGGARA PROVINCE FROM 2021 TO 2023 - Ambar Wati, Tri Surya; Murtanto (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2026)
This study analyzes fluctuations in regional tax revenue in East Nusa Tenggara Province in relation to tourism sector development during the 2021–2023 period. Using a quantitative explanatory approach with panel data regression, this research examines the effect of the number of tourists, the number of restaurants, and hotel occupancy rates on regional tax revenue across regencies and cities. The study uses secondary data obtained from official publications of the Central Statistics Agency and local government institutions. The novelty of this research lies in its focus on regional tax revenue rather than overall regional original revenue and its emphasis on East Nusa Tenggara Province, which has distinct tourism characteristics. The results show that the number of tourists and hotel occupancy rates have a positive and significant effect on regional tax revenue, while the number of restaurants has a positive but insignificant effect. Simultaneously, all tourism variables significantly influence regional tax revenue, indicating that improving tourism quality, particularly by increasing hotel occupancy, is more effective in enhancing regional tax revenue.